2001
DOI: 10.1007/s002590100649
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of inhomogeneity in ventilation SPET

Abstract: The aim of this study was to evaluate a method for quantification of inhomogeneity in ventilation single-photon emission tomography (SPET). Nine emphysematous patients, nine life-long non-smokers and nine smokers were included in the study. The SPET investigation was performed after 50 MBq (99m)Tc-Technegas had been inhaled by each subject in the supine position. A single-head gamma camera, equipped with a general-purpose parallel-hole collimator using 64 projections (20 s each) over 360 degrees, was used. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Several recent SPECT studies have evaluated objective estimates of ventilation heterogeneity in normal and diseased lung (57,97). For example, Xu et al (97) showed that intraand interregional ventilation heterogeneity discriminated between normal and emphysematous lungs.…”
Section: Ventilation Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent SPECT studies have evaluated objective estimates of ventilation heterogeneity in normal and diseased lung (57,97). For example, Xu et al (97) showed that intraand interregional ventilation heterogeneity discriminated between normal and emphysematous lungs.…”
Section: Ventilation Heterogeneitymentioning
confidence: 99%
“…For example, Xu et al (97) showed that intraand interregional ventilation heterogeneity discriminated between normal and emphysematous lungs.…”
Section: Ventilation Heterogeneitymentioning
confidence: 99%
“…My work towards this objective can be divided into the following specific aims  Evaluation of reconstruction methods for subjective visual evaluation of lung SPECT images.  Improving the methodology introduced by Xu (Xu et al, 2001a) of extracting CV values out of a lung ventilation SPECT image.  Evaluating the ability of the CV T -method to differentiate between uniform and heterogeneous ventilation distributions using a anthropomorphic phantom.…”
Section: Aim Of the Thesismentioning
confidence: 99%
“…Xu presented in 2001 (Xu et al, 2001a), regional heterogeneity measurements determined by calculating the coefficient of variation (CV) in small ele-ments of the lung. Heterogeneity maps and frequency curves were generated based on the CV values from ventilation SPECT images of nine emphysematous patients, nine healthy smokers and nine healthy non-smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Ventilation scans, however, have been adapted for studies of ventilation in airways disease (King et al, 1997and 1998, 4 Downie et al, 2007. SPECT imaging offers the potential to characterise the topographical distribution of ventilation so that inhomogeneity can be quantified at the regional level (Xu et al, 2001, Venegas et al, 2005. Combining imaging information with the pulmonary function measures of inhomogeneity will provide important information about the ventilatory abnormalities in asthma and COPD (Tgavalekos et al, 2007, Berend et al, 2008.…”
Section: Introductionmentioning
confidence: 99%